Strike a happy medium - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
When you re a smallholder farmer, it is not always easy to get your inputs since many traders only sell in bulk, charge extra for small quantities or only sell in towns and cities. Being an independent and a small rural business, making contact...